Vector Quantization Techniques For Partial Encryption of Wavelet-based Compressed Digital Images - Younis, Dr. Hameed A.; Abdalla, Dr. Turki Y.; Abdalla, Dr. Abdulkareem Y. (Iraqi Journal for Electrical and Electronic Engineering, 2009)
The use of image communication has increased in recent years. In this paper, new partial encryption schemes are used to encrypt only part of the compressed data. Only 6.25-25% of the original data is encrypted for four different images, resulting in a significant reduction in encryption and decryption time. In the compression step, an advanced clustering analysis technique (Fuzzy C-means (FCM)) is used. In the encryption step, the permutation cipher is used. The effect of number of different clusters is studied. The proposed partial encryption schemes are fast and secure, and do not reduce the compression performance of the underlying selected compression methods as shown in experimental results and conclusion.